2022
DOI: 10.3389/pore.2022.1610055
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Sequence Analysis in Patients With Kaposi’s Sarcoma-Associated Herpesvirus

Abstract: MicroRNAs (miRNAs) are the non-coding RNAs that can both attach to the untranslated and coding sections of target mRNAs, triggering destruction or post-transcriptional alteration. miRNAs regulate various cellular processes such as immune function, apoptosis, and tumorigenesis. About 35,000 miRNAs have been discovered in the human genome. The increasing evidence suggests that the dysregulation of human miRNAs may have a role in the etiology of some disorders including cancer. Only a small sub-set of human miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Highly expressed miRNAs may act as oncogenes by suppressing tumor suppressor genes, while miRNAs expressed at low levels may function as tumor suppressors by negatively regulating oncogenes [ 6 ]. Recent studies have described miRNA signatures in KS, with several miRNAs found to be downregulated or upregulated [ 7 , 8 ] as a mediator in the virus-host interaction network of KS [ 9 ]. These miRNAs have the potential to serve as biomarkers for KS diagnosis, prognosis prediction, and as targets for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Highly expressed miRNAs may act as oncogenes by suppressing tumor suppressor genes, while miRNAs expressed at low levels may function as tumor suppressors by negatively regulating oncogenes [ 6 ]. Recent studies have described miRNA signatures in KS, with several miRNAs found to be downregulated or upregulated [ 7 , 8 ] as a mediator in the virus-host interaction network of KS [ 9 ]. These miRNAs have the potential to serve as biomarkers for KS diagnosis, prognosis prediction, and as targets for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are compact RNA molecules, typically around 22 nucleotides in length, which act as antisense RNA to suppress the post-transcriptional expression of target genes [ 4 ]. Dysregulation of miRNAs causes several human diseases, including OC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%